Pengaruh Penggunaan Aplikasi Google Classroom terhadap Hasil Belajar Siswa Kelas X di SMK LAB SCHOOL UNESA - Ahmad Wahib Hilmi; Deddy Setiawan; Muhammad Miftah Farid (Universitas Negeri Surabaya, 2022)
The purpose of this study was to determine: the effect of using the google classroom application on student learning outcomes. In Indonesia, distance or online learning begins on March 16, 2020, where children start learning from their own homes without the need to go to school. Choosing the right application will affect students' interest in learning (Wulandari, 2016), which is usually done by giving assignments personally to students which tends to reduce student interest in learning. The learning process through Google Classroom is very easy to do.Various conveniences are indeed presented by today's technological advances that support the realization of more effective learning. In this study, the researchers focused on the use of google classroom learning media. The use of the google classroom application at this school is used as a medium in carrying out learning. The research method used is descriptive quantitative method. The sampling technique used was purposive sampling. The results of this study prove that there is an effect of google classroom on student learning outcomes, this is evidenced by the results of the paired sample test showing that H0 is rejected and Ha is accepted which shows that there are differences between pretest and posttest before and after using the google classroom application which shows that by using the google classroom application student learning outcomes can be increased.